Permissionless Innovation. - Chesbrough, Henry; Van Alstyne, Marshall (Communications of the ACM, 2015)
The article explains the importance of permissionless innovation to the pharmaceutical industry. According to the authors, the industry could benefit from this new approach to research and development. They suggest the creation of rules that apply to platforms that promote innovation and the development of technology that benefits from open access like application program interfaces (APIs). The industry is advised to use permissionless innovation to discover new drugs.